Pengaruh Sosialisasi Perpajakan, Sanksi Pajak, Dan Kualitas Layanan Perpajakan Terhadap Kepatuhan Wajib Pajak Hotel, Restoran, Dan Hiburan Di Kota Makassar - Yusran Mansyur; Sylvia Sjarlis; Zainal Abidin (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2023)
This study aims to determine and analyze the effect of tax socialization, tax sanctions and taxpayer compliance at the Makassar City Regional Revenue Agency. The type of research is quantitative with a survey approach. This research was conducted at the Regional Revenue Agency with a research time of 2 months. This study used a survey by distributing questionnaires. The population used is the taxpayers. The sampling technique used the Hair formula where 360 samples were obtained. The analytical method used is Multiple Linear Regression Analysis. The results of this study prove that tax socialization, tax sanctions and taxpayer compliance have a positive and significant effect on taxpayer compliance in Makassar City. The coefficient of determination in this study is 14.1%.